Patrimoine culturel sarmate dans l’espace social du Duché de Lorraine et de Bar sous le règne du roi Stanisław Leszczyński (1737-1766), expression de l’identité culturelle polonaise - Durbas, Małgorzata (Studia Europaea Gnesnensia, 2023)
The aim of the article is to discuss the Sarmatian cultural transfer into the social space of Lor-raine as a manifestation of the Polish cultural identity of the king of Poland, duke of Lorraine and Bar, Stanislaus Leszczynski, a European and a citizen of the world. Leszczynski’s prolific contributions in his new homeland had its roots in the Sarmatian culture, one in which he grew up and which became ingrained in his consciousness. Through the Polish monarch and his Polish entourage, elements of Polish cultural identity—profoundly anchored in the Sarmatian background—began to permeate into the social space of the new homeland of Lorraine.